Evaluation of Time and Color Perception in Children and Adults - Sertaç Üstün; Merve Akın; Furkan Atakan Akın; Serkan Tokgönül; Metehan Çiçek (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Objectives:The study aimed to compare the time and color perception among adults and children to reveal the age-dependent change of the time perception.Materials and Methods:The children (n=30; age: 7-12, 50% female) and the adults (n=30, age: 20-25, 60% female) were selected randomly to participate to the study. To evaluate the time and color perception ‘‘Foreperiod Task’’ which was designed via MATLAB software was used. The percentage of correct responses and reaction times of participants were obtained to evaluate participants’ performance.Results:The percentage of correct responses and reaction times data were analyzed with two-way ANOVA separately. For the percentage of correct response; task effect (F=83.56, p<0.001), group effect (F=94.34, p<0.001) and task-group interaction (F=7.56, p<0.05) were significant. For the reaction time; group effect was significant (F=22.09 p<0.001). Task effect and interaction of task-group were not significant. Reaction times in time and color perception tasks were not different from each other both in adult groups and children groups (p>0.05). However, the percentage of correct responses for the two tasks differed significantly in both groups (for children: t=5.5, p<0.001; for adults: t=8.3, p<0.001).Conclusion:Performance score of the children was lower than adults in both tasks. Participants’ time perception performances were lower than their color perception and this performance difference was more distinct in children compared to adults. These results indicate that the development of time perception in children is slower than color perception. The fact that relatively complex neural networks are involved for the timing process in the brain might be the reason for the slow development of the time perception.